Analisis Modal Sosial Masyarakat Dalam Pencegahan Kebakaran Lahan Gambut Di Desa Kundur Kecamatan Tebing Tinggi Barat Kabupaten Kepulauan Meranti - Amami, Syahilla; Yulida, Roza; Andriani, Yulia (Journal of Agribusiness and Community Empowerment (JACE), 2022)
Peatland fire is a condition where peatland is hit by fire, causing damage that causes economic and environmental losses. One of the efforts to prevent peatland fires is through social capital. The purpose of this study was to find out the programs carried out by the government with the Fire Care Community (MPA) in peatland management and to analyze the social capital of the community in efforts to prevent peatland fires. This research was conducted in Kundur Village, Tebing Tinggi Barat District, Meranti Islands Regency. The number of respondents in this study was 60 people obtained using the purposive sampling method. The data that has been obtained is then analyzed using qualitative methods with descriptive analysis and quantitative analysis with average analysis. The results of the study show that the programs carried out by the government and the community are establishing a Fire Care Community (MPA), processing peat water to obtain clean drinking water through the Pamsimas program, the government also socializing fire prevention which is one of the efforts to prevent land fires. peat in Kundur Village, and the Sago-Based Pilot Project program. The analysis of social capital shows that MPA members are still not optimal in implementing ancestral values in Kundur Village, for example, it can be seen that in terms of interests there are still some MPA members who prioritize personal interests, compared to common interests in efforts to overcome land fires in the village. Kundur, for example, when the meeting schedule was held, some MPA members were not present and preferred to work taking care of their agricultural land. Furthermore, there are still MPA members who feel they have been treated unfairly in giving their opinions, and finally the lack of proactive action by MPA members in carrying out programs related to efforts to overcome land fires in Kundur Village.